Strategi Meningkatkan Loyalitas Nasabah Bank Syariah: Perspektif Kualitas, Kepercayaan, dan Religiusitas - Mumtaz, Alisa Hana; Jaharuddin, Jaharuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the influence of service quality, trust, satisfaction, and religiosity on customer loyalty, considering perceived value as a mediating variable. The research was conducted on Islamic bank customers in Indonesia, specifically in the Special Capital Region of Jakarta, using a quantitative approach based on the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The study collected data from 292 respondents, with 252 meeting the research criteria. The results indicate that satisfaction, service quality, and religiosity have a positive and significant impact on perceived value, whereas customer trust does not have a significant effect. Furthermore, perceived value has been proven to have a strong influence on customer loyalty. The mediation analysis shows that perceived value significantly mediates the relationship between service quality, satisfaction, and religiosity with customer loyalty, while the relationship between customer trust and loyalty is not mediated by perceived value. These findings confirm that improving service quality, customer satisfaction, and religiosity aspects can enhance customers' perceived value, ultimately leading to greater loyalty. Therefore, Islamic banking institutions should prioritize strategies focused on improving service quality, fulfilling customer satisfaction, and addressing religiosity aspects to enhance perceived value and customer loyalty in the long term.